IMPLEMENTASI KEBIJAKAN PEMBERANTASAN PENYAKIT DEMAM BERDARAH DENGUE DI KABUPATEN KARIMUN - Ricky Bernardo Rajagukguk; Nur Laila Meilani (Halu Oleo University, 2023)
In Indonesia, Dengue Hemorrhagic Fever, or DHF has long been known as an infectious disease that can spread the dengue virus to a group of people and cause an epidemic that disrupts the social life of the residents of the area. In the Kepulauan Riau Province, Karimun Regency is one of the districts with the most dengue cases. This study seeks to find out how the implementation of the policy of eradicating dengue hemorrhagic fever in the Karimun Regency and what factors hinder its implementation. This research used a descriptive qualitative research method with a phenomenological approach. The theoretical concepts used are from the Edward III policy implementation theory model as a theoretical concept with indicators that can influence policy implementation, namely Communication, Resources, Disposition, and Bureaucratic Structure. The results of research on the implementation of DHF eradication policies in Karimun Regency have not gone well, this is evidenced by the suboptimal eradication movement, the use of larvicides that are not implemented properly, and the lack of public awareness regarding eradicating mosquito nests. The government must launch the 1 House 1 jumantik movement again so that the DHF eradication policy can be implemented properly.